Mesenteric abscess presents as left iliac fossa mass in postoperative case of inguinal hernia surgery with undescended testis - Mahajan, Monalisa (International Surgery Journal, 2020)
An abscess is a collection of pus (dead and dying neutrophils plus proteinaceous exudate) that has built up within the tissue of the body. Mesenteric abscess is a rare, usually accounts for small percentage of intra-abdominal abscess after inguinal hernia surgery which is presented as left iliac fossa mass in postoperative period of open inguinal hernia surgery of left side and also presented with undescended testis of left side which is actual cause of formation of inguinal hernia of same side. Late onset mesh infection and post-operative peritonitis are very common in case of open hernia surgery. Intra-abdominal abscess cause significant morbidity and mortality. Surgery disturb the equilibrium between coagulation and fibrinolysis in the abdominal cavity in favour of coagulation system. Diminished fibrin degradation is a common pathway for the formation of abscess. We present a case of 40 years of male came with pain in left iliac fossa and lower abdomen for last 2 months with a swelling at LIF and hypogastric region for last 3 months with a previous history of hernia surgery of left side 2 month back which was diagnosed as mesenteric abscess and treated with exploratory laparotomy under general anaesthesia and abscess was drained.